Android Server For Wlan Control And Management (International Journal of Engineering and Computer Science, 2017)
LAN monitoring and controlling system is a computer system which would enable the lab administrator to interact with other user computers and the users as well. It enables the administrator to remotely control the all client system from our android mobile. Using this system administrator doesn’t need to be physically present at the user computer to monitor them or to solve their problems. Administrator would be remotely monitoring all the user computers in the laboratory sitting at his desk, which would greatly increase the efficiency of the work being performed and would include remote technical support. Lab Monitoring and controlling System is platform independent resulting in monitoring and interaction of all the systems in the laboratory where it is installed, independent of type of Operating System installed on it. The primary function of a LAN monitoring and controlling system is the ability to remotely operate one computer from another computer over a network.